Gastric enzymes as a screening test for gastric cancer. Issue 3 (March 1987) - Finch, P J; Ryan, F P; Rogers, K; Holt, S
Abstract : Levels of lactic dehydrogenase and beta-glucuronidase were measured in gastric wash samples obtained from 445 patients over 40 years old attending a routine diagnostic endoscopy clinic. An index was derived from the two levels and used as a test for the presence of gastric cancer. Of the 24 patients with an endoscopic diagnosis of gastric cancer, 21 (91.3%) proved positive on this test, including all four cases of early gastric cancer, which were found at repeat endoscopy. The specificity of the test for gastric cancer was 81.3%. Among those patients with false positive results who had endoscopic biopsy were four out of the five cases of severe dysplasia, and four out of the 13 cases of type 2B intestinal metaplasia. Atrophic gastritis alone or with intestinal metaplasia was found in 95.9% of the false positives who were biopsied.